Approaches to determining occlusion pressure for blood flow restricted exercise training: Systematic review. Issue 6 (19th March 2021) - Murray, James; Bennett, Hunter; Boyle, Terry; Williams, Marie; Davison, Kade
ABSTRACT: Low-intensity exercise with blood flow restriction (BFR) is an increasingly common method of improving muscular strength and hypertrophy, and improving aerobic fitness, in clinical and athletic populations. The aim of this systematic review was to describe common approaches to determining occlusion pressures for BFR exercise. A comprehensive literature search yielded 1389 results, of which 129 were included. Studies were predominantly randomised control trials (86.7%) with modest sample sizes (average number of 11.4 ± 6.2 participants per BFR group/s) of young adults (average age of 34.6 ± 17.9). Five different approaches for determining occlusion pressure were identified: arbitrary pressures (56.6%), percentage of limb occlusion pressure (25.6%), brachial systolic blood pressure (10.9%), perceived tightness (3.9%) and other (3%). From 2016 to 2018, the number of published papers using a percentage of limb occlusion pressure increased yearly, paralleling a decrease use of arbitrary pressures. Of the studies included in this review, the most common approach to determining occlusion pressure was using a non-individualised, arbitrary pressure. Given the safety concerns associated with arbitrary pressures, continual dissemination regarding the optimal applications of BFR for safety and efficacy is required.